The water-energy-food nexus: climate risks and opportunities in southern Africa - Nhamo, Luxon; Ndlela, B.; Nhemachena, Charles; Mabhaudhi, Tafadzwanashe; Mpandeli, S.; Matchaya, Greenwell C. (MDPI, 2018)
The discourse on the need for water, energy, and food security has dominated the development agenda of southern African countries, centred on improving livelihoods, building resilience, and regional integration. About 60% of the population in the Southern African Development Community (SADC) live in rural areas relying mainly on rainfed agriculture, lacking access to clean water and energy, yet the region is endowed with vast natural resources. The water-energy-food (WEF) nexus is a conceptual framework that presents opportunities for greater resource coordination, management, and policy convergence across sectors. This is particularly relevant in the SADC region as resources are transboundary and supports efforts linked to regional integration and inclusive socio-economic development and security. We conducted an appraisal of WEF-related policies and institutions in SADC and identified linkages among them. The present ‘silo’ approach in resource management and allocation, often conducted at the national level, contributes to the region’s failure to meet its development targets, exacerbating its vulnerabilities. The lack of coordination of WEF nexus synergies and trade-offs in planning often threatens the sustainability of development initiatives. We highlighted the importance of the WEF nexus to sustainably address the sectoral coordination of resources through harmonised institutions and policies, as well as setting targets and indicators to direct and monitor nexus developments. We illustrate the significance of the nexus in promoting inclusive development and transforming vulnerable communities into resilient societies. The study recommends a set of integrated assessment models to monitor and evaluate the implementation of WEF nexus targets. Going forward, we propose the adoption of a regional WEF nexus framework.